The robot builder's cookbook - Bishop, O. N. (Owen Neville) (Elsevier/Newnes, 2007)
Owen Bishop introduces, through hands-on project work, the mechanics, electronics and programming involved in practical robot design-and-build. The use of the PIC microcontroller throughout provides a painless introduction to programming whilst harnessing the power of a highly popular microcontroller used by students and design engineers worldwide. This is a book for first-time robot builders, advanced builders wanting to know more about programming robots and students in Further and Higher Education tackling microcontroller-based practical work. They will all find this book a unique and exciting source of projects, ideas and techniques, to be combined into a wide range of fascinating robots. · Full step-by-step instructions for 5 complete self-build robots · Introduces key techniques in electronics, programming and construction - for robust robots that work first time · Illustrations, close-up photographs and a lively, readable text make this a fun and informative guide for novice and experienced robot builders.